2019
DOI: 10.1111/nph.16071
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification of EMBRYODEFECTIVE (EMB) genes required for growth and development in Arabidopsis

Abstract: Summary With the emergence of high‐throughput methods in plant biology, the importance of long‐term projects characterized by incremental advances involving multiple laboratories can sometimes be overlooked. Here, I highlight my 40‐year effort to isolate and characterize the most common class of mutants encountered in Arabidopsis (Arabidopsis thaliana): those defective in embryo development. I present an updated dataset of 510 EMBRYO‐DEFECTIVE (EMB) genes identified throughout the Arabidopsis community; includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(103 citation statements)
references
References 207 publications
(243 reference statements)
2
87
1
Order By: Relevance
“…9 ). The slight accumulation of abundant RPL3A, an essential gene for Arabidopsis (Meinke, 2019), appears to compensate reduction of RPL3B in our study. In addition, RPL3B decrease in the absence of REIL proteins has a transcriptional component, as the reduction of RPL3B transcript is one of the rare observations of otherwise absent associations between transcriptome and proteome changes of non-translating fractions ( Supplemental Figure S9 ).…”
Section: Discussionsupporting
confidence: 55%
“…9 ). The slight accumulation of abundant RPL3A, an essential gene for Arabidopsis (Meinke, 2019), appears to compensate reduction of RPL3B in our study. In addition, RPL3B decrease in the absence of REIL proteins has a transcriptional component, as the reduction of RPL3B transcript is one of the rare observations of otherwise absent associations between transcriptome and proteome changes of non-translating fractions ( Supplemental Figure S9 ).…”
Section: Discussionsupporting
confidence: 55%
“…Seed development is controlled by programmed gene expression. To date, many genes have been identified and characterized as being important for seed development [156]. The research in the last decade has shown epigenetics is important for seed development, but it remains largely unclear how different epigenetic mechanisms interact to regulate seed development.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recently, an updated list of 510 EMBRYO-DEFECTIVE (EMB) genes was presented [41], which contains several flavoenzyme-encoding genes. We detected six flavoenzyme-encoding genes (AT1G24340, AT1G48850, AT1G49880, AT3G02280, AT3G54660, AT5G14760), which are assigned to be essential for embryo development [42][43][44][45][46].…”
Section: Flavoproteins Localization and Fmn/fad Distributionmentioning
confidence: 99%
“…AT1G24340 is predicted to encode a FAD-dependent flavoenzyme (see the third evidence code). Considering that the list of EMB genes is not complete (as 750-1000 EMB genes are estimated in Arabidopsis [41]), it is assumed that more flavoenzymes are essential for embryo development. In continuation, a list of embryo-lethal double mutants (embryo lethality only in combination of two mutated genes) was published.…”
Section: Flavoproteins Localization and Fmn/fad Distributionmentioning
confidence: 99%